2020
DOI: 10.1097/coc.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Six-Week Interval Between Preoperative Radiation and Surgery Is Associated With Fewer Major Wound Complications in Soft Tissue Sarcoma

Abstract: Objectives: A total of 30% to 40% of soft tissue sarcoma (STS) patients develop major wound complications (MWCs) after preoperative radiation (preRT). The optimal preRT-surgery interval and its association with MWCs is unknown. This study investigated whether a longer preRT-surgery interval is associated with fewer MWCs compared with historical controls. Methods: All patients treated by a single surgeon after preRT with limb-sparing wide resection for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…The soft tissue complication rate in our study was found to be lower compared to the current literature, where rates range from 10.6% to 41% 17–20 . In addition, several studies investigating soft tissue sarcomas specifically, have found an association between increased sarcoma size and incidence of surgical complications 21–23 .…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The soft tissue complication rate in our study was found to be lower compared to the current literature, where rates range from 10.6% to 41% 17–20 . In addition, several studies investigating soft tissue sarcomas specifically, have found an association between increased sarcoma size and incidence of surgical complications 21–23 .…”
Section: Discussioncontrasting
confidence: 65%
“…The soft tissue complication rate in our study was found to be lower compared to the current literature, where rates range from 10.6% to 41%. [17][18][19][20] In addition, several studies investigating soft tissue sarcomas specifically, have found an association between increased sarcoma size and incidence of surgical complications. [21][22][23] Larger tumors require a corresponding larger resection or excision procedure, which leads to an increase in dead space volume and greater potential for the development of seroma, hematoma, or devitalized tissue.…”
Section: Multivariate Logistic Regression Analysismentioning
confidence: 99%
“…A recent meta-analysis of 21 studies and more than 5,000 patients operated for extremity STS, identified an overall wound complication rate of 30% and a reoperation rate of 13%. [42][43][44] The type of surgical procedure strongly influences postoperative complications rate and resource burden. For example, in a study of 78 patients who underwent hindquarter amputation wound complication rate was 49%, in-hospital mortality was 6%, and median hospital stay was 24 days.…”
Section: Metastatic Gistmentioning
confidence: 99%
“…A recent meta‐analysis of 21 studies and more than 5,000 patients operated for extremity STS, identified an overall wound complication rate of 30% and a reoperation rate of 13% 42‐44 . The type of surgical procedure strongly influences postoperative complications rate and resource burden.…”
Section: Sts Of the Extremity And Trunkmentioning
confidence: 99%
“…Soft tissue sarcoma is most often treated with preoperative radiotherapy followed by surgery for local control [1,[8][9][10]12]. Radiation is preferred before surgery, as the functional results of the salvaged limb have been demonstrated to be superior when compared with radiation administered after surgery [10,13].…”
Section: Introductionmentioning
confidence: 99%